The impact of exclusive breastfeeding and timely complementary feeding on the nutritional status of toddlers - Boy, Elman; Hasibuan, Rudi Iskandar; Rasyid , Ashil Muhammad Abdul; Ilhamsyah , Nugraha; Shafira, Cut Shanaz Dhiya; Hendewi, Annisa Fitri; Pranata, Raudatul Husna; Harun, Putri Maulia Amami (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2023)
Background: Breast milk and complementary feeding are important sources of nutrition in the first 1000 days of life, so nutritional deficiencies in this period of life cause problems in both short and long terms. Hence, investigating the association between breastfeeding, complementary feeding history, and toddlers’ nutritional status is important. Objective: This study aims to assess the influence of exclusive breastfeeding and timely complementary feeding on the nutritional status of children under five. Methods: This cross-sectional study was conducted in a Public Health Centre (Puskesmas) in Medan, North Sumatera. Data regarding the toddlers’ height and weight were obtained through direct measurements, whereas information about breastfeeding and complementary feeding history was gathered through interviews with the toddlers’ mothers. Chi-square analysis was performed for statistical analysis. Results: The study involved 50 toddlers, 30 boys and 20 girls. Among them, 58% received both exclusive breastfeeding and timely complementary feeding, while 42% did not. Among toddlers who received exclusive breastfeeding and timely complementary feeding, 82.7% demonstrated normal nutritional status, whereas 10% experienced malnutrition. Conversely, in toddlers not given exclusive breastfeeding and timely complementary foods, only 38% had normal nutrition, with the remaining 62% facing malnutrition. There was an association between exclusive breastfeeding, timely complementary feeding, and toddlers’ nutritional status (P < 0.05). Toddlers receiving exclusive breastfeeding had 7.8 times higher odds of experiencing normal nutritional status compared to those without it. Similarly, toddlers exposed to timely complementary feeding had 4.3 times higher odds of experiencing normal nutrition. Conclusion: Exclusive breastfeeding and timely complementary feeding played an important role in the nutritional status of toddlers.